Numerical responses in resource-based mutualisms: A time scale approach - Revilla, Tomás A (Journal of theoretical biology, 2015)
Many mutualisms involve inter-specific resource exchanges, making consumer-resource approaches ideal for studying their dynamics. Also in many cases these resources are short lived (e.g. flowers) compared with the population dynamics of their producers and consumers (e.g. plants and insects), which justifies a separation of time scales. As a result, we can derive the numerical response of one species with respect to the abundance of another. For resource consumers, the numerical responses can account for intra-specific competition for mutualistic resources (e.g. nectar), thus connecting competition theory and mutualism mechanistically. For species that depend on services (e.g. pollination, seed dispersal), the numerical responses display saturation of benefits, with service handling times related with rates of resource production (e.g. flower turnover time). In both scenarios, competition and saturation have the same underlying cause, which is that resource production occurs at a finite velocity per individual, but their consumption tracks the much faster rates of population growth characterizing mutualisms. The resulting models display all the basic features seen in many models of facultative and obligate mutualisms, and they can be generalized from species pairs to larger communities.
Keywords: populační dynamika; symbióza; ekosystém; Models, Biological; Symbiosis; biologické modely; opylení; Pollination; šíření semen; Animals; Seed Dispersal; zvířata; Ecosystem; Population Dynamics